EMOTIONAL NEGLIGENCE: A PSYCHOANALYTICAL STUDY ON COLLEEN HOOVER’S VERITY - Brindha, N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Childhood maltreatment is commonly described as physical, sexual or emotional abuse and physical or emotional neglect by parent, caregiver or other adult, with all kinds of abuse resulting from acts of commission, and neglect from acts of omission. There has been relatively less societal and research attention on emotional abuse and emotional neglect, compared with physical and sexual abuse and physical neglect. The emotional neglect manifest in the individual’s daily life though unconsciously as anger outburst, resentment/hatred, bitterness, poor relations with the peers and parents, low self-confidence, cannot handle criticism, rebellion, poor academic performance, loneliness, mistrust, fear, feelings of inadequacy, drug and substance abuse and in extreme cases hopelessness, depression and suicidal tendencies. The study on the novel Verity recommends the empowerment of the children to accept themselves, express their thoughts and feelings, and create awareness among parents and caregivers to be responsive to children’s thoughts and feelings therefore promote holistic growth.